Winter canola yield and nitrogen use efficiency in a semiarid irrigated condition. (9th March 2021) - Paye, Wooiklee S.; Begna, Sultan; Ghimire, Rajan; Angadi, Sangamesh V.; Singh, Paramveer; Umesh, Mathada Rangappa; Darapuneni, Murali
Abstract: Winter canola ( Brassica napus L.) is an economically viable alternative crop for the semiarid southern Great Plains of the United States. Although land area under winter canola has increased in recent years, an independent guideline on fertility recommendation and their effects on crop growth and soil health is not available for the semiarid southern Great Plains region. This study aimed to evaluate winter canola growth, yield components, and nitrogen use efficiency (NUE) with different nitrogen application timings (NATs) in a semiarid irrigated condition. A 2‐yr study was designed with two canola varieties (Riley and 46W94) and four NATs. Nitrogen treatments were F100 (100% of nitrogen applied in fall), S100 (100% of nitrogen applied in spring), FS50 (50% of nitrogen applied in fall and 50% in spring), and FSB25 (25% of nitrogen applied in fall, 25% in spring, and 25% before flowering). The winter dry matter accumulation was greater with the F100 N application, whereas the forage quality was better with the FS50 treatment. The highest seed yield of 2, 539 kg ha –1 was from S100, which was not significantly different from FS50 and FSB25. The N use efficiency was the highest under FSB25, which uses 25% less N, followed by S100, FS50, and F100 treatments. The FS50 with 50% of N application in fall and 50% in spring was the most efficient N timing treatment when winter biomass accumulation, seed yield, and seed oil and protein contents were considered. Core Ideas: Improved fertility management is crucial for the high yield and quality of winter canola. Split application of N improved nutritive value in biomass and seed oil content. FS50 produced high fall biomass, as well as seed yield, oil, and seed protein contents. The FSB25, with 25% less N application, had the highest N use efficiency.